IMPLEMENTASI METODE CARD SHORT DALAM PEMBELAJARAN BAHASA ARAB SISWA KELAS X MA DARUL ARQAM GOMBARA SULAWESI SELATAN - Dyah Astri Eka; Mahlani Sabae (Universitas Muhammadiyah Makassar, 2018)
This study aims to determine how effective the implementation of Arabic learning, especially kitabah and mufradat by using the card short method in class X MA Darul Arqam Muhammadiyah Gombara as well as supporting and inhibiting factors in the realization of the Arabic learning process using the short card method. The type of research used is Classroom Action Research using two cycles. Data collection methods used are observation and tests with instruments of observation sheets and test of learning outcomes. The data analysis technique was carried out by comparing the results of the notes carried out by the researchers themselves with collaborators' notes with these comparisons.The results of this study indicate that the implementation of card short media in the learning of kitabah and mufradat in the MA Darul Arqam Muhammadiyah Gombara South Sulawesi took place effectively. The supporting factors for the card short method are beautiful images and bright colors. Students are more happy in learning because the learning process using short card media invites students to learn while playing so students are not stressed by learning. The inhibiting factor is when learning takes place in the classroom becomes crowded because students play to find the meaning of the mufrodhat.Keywords: Card Short Method, Kitabah, Mufradat